Pengaruh Biaya Dan Jumlah Produksi Terhadap Pendapatan Petani Buah Naga Di Desa Kendalrejo Kecamatan Tegaldlimo Kabupaten Banyuwangi - Muzaki, Ahmad; Meitriana, Made Ary (Universitas Pendidikan Ganesha, 2024)
The research aims to determine the effect of costs and amount of production on the income of dragon fruit farmers in Kendalrejo Village, Tegaldlimo District, Banyuwangi Regency. This research uses quantitative research methods with survey research type with data collection using observation, questionnaires and interviews. The respondents of this research were 90 dragon fruit farmers who were ready to harvest. The data from this research was processed using SPSS version 23. The results of this research using a significance level of 5% show that costs do not have a significant effect on the income of dragon fruit farmers. with sig value. 0.336 < 0.05. Meanwhile, the amount of production has a significant effect on farmer income with a sig. 0.000 < 0.05. Taken together, costs and production quantities have a significant effect on farmers' income with a value of sig. 0.000 < 0.05. Costs and amount of production variables influence the income variable by 60.8%, whereas the remaining 39.2% is influenced by other variables not examined in this research.